P14.110 Primary leptomeningeal melanocytic tumors - clinical course and molecular pathological aspects of an underestimated entity. (6th September 2019) - Dohmen, H; Jensen, A; Schoeller, K; Uhl, E; Acker, T; Stein, M
Abstract: BACKGROUND: Primary leptomeningeal melanocytic tumors (PLMT) of the central nervous system are extremely rare, usually benign pigmented tumors. The aim of our study is to present two complex cases of PLMT with discussion of clinical and molecular aspects. MATERIAL AND METHODS: Medical charts of two patients from our institution with PLMT were reviewed. Oncogenic common gene mutations in GNAQ (Q209, exon 5), GNA11 (Q209, exon 5), TERT promoter and BRAF (exon 11, 15) were analyzed and a genome-wide DNA methylation array (Infinium Human-MethylationEPIC BeadChip) was performed. Brain tumors were categorized according to their DNA methylation profile using the brain tumor classifier algorithm (https://www.molecularneuropathology.org/mnp ). RESULTS: Case1: A 15 year-old boy presented with a large tumor in the in the cerebellopontine angle with extension to the cavernous sinus and the middle fossa in June 2013. Consequently, partial resection of the PLMT was performed followed by photon radiation therapy. First recurrence developed after 12 months. Despite reradiation with proton therapy, reresection, and several chemotherapies the patient died 4 years and 3 month after initial diagnosis. Histopathological examination of the resected tumor sample revealed a pigmented neoplasm with epithelioid cells with strong expression of melanocytic markers Melan A and HMB 45. In the recurrent biopsy samples, an increase in the Ki-67/MIB index from 2 to 10 % was observed. Molecular analysis showed a characteristic GNA11 Q209L mutation that supports the diagnosis of PLMT. Case2: In April 2016 the resection of a PLMT in a 42 year-old female in the pinealis region was performed. First recurrence developed after 21 months and reresection followed by proton therapy was performed. A distant tumor developed 7 month later and after resection the patient received local proton therapy. Only 1 month later a new tentorial tumor was detected and treated by proton therapy. Tumor tissue of the local recurrence showed focal epitheloid cell morphology with brain invasion, tumor necrosis and increased mitotic activity. KI-67/MIB1 index was approximately 3% in the first and above 10 % in the second and third operation. The hotspot mutation in GNAQ Q209L was found in all tumor samples. In addition to histological signs of malignancy, an increase in chromosomal aberrations was seen at recurrence as a sign of malignant progression. To-date the patient is alive but new cranial metastases were detected. CONCLUSION: Though PLMT is defined as benign lesion, the treatment is complicated by early local recurrence as well as intracranial and spinal metastases. For the first time malignant transformation during the clinical course of PLMT was confirmed by histology and DNA methylation array.